Bounds on an anomalous dijet resonance in W+jets production in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (American Physical Society (APS), 2011)
We present a study of the dijet invariant mass spectrum in events with two jets produced in association with a W boson in data corresponding to an integrated luminosity of 4.3fb-1 collected with the D0 detector at √s=1.96TeV. We find no evidence for anomalous resonant dijet production and derive upper limits on the production cross section of an anomalous dijet resonance recently reported by the CDF Collaboration, investigating the range of dijet invariant mass from 110 to 170GeV/c2. The probability of the D0 data being consistent with the presence of a dijet resonance with 4 pb production cross section at 145GeV/c2 is 8×10-6.